Amplification of TGFβ Induced ITGB6 Gene Transcription May Promote Pulmonary Fibrosis - Tatler, Amanda L. (PLoS One, 2016)
Idiopathic pulmonary fibrosis (IPF) is a devastating, progressive disease with poor survival rates and limited treatment options. Upregulation of αvβ6 integrins within the alveolar epithelial cells is a characteristic feature of IPF and correlates with poor patient survival. The pro-fibrotic cytokine TGFβ1 can upregulate αvβ6 integrin expression but the molecular mechanisms driving this effect have not previously been elucidated. We confirm that stimulation with exogenous TGFβ1 increases expression of the integrin β6 subunit gene (ITGB6) and αvβ6 integrin cell surface expression in a time- and concentration-dependent manner. TGFβ1-induced ITGB6 expression occurs via transcriptional activation of the ITGB6 gene, but does not result from effects on ITGB6 mRNA stability. Basal expression of ITGB6 in, and αvβ6 integrins on, lung epithelial cells occurs via homeostatic αvβ6-mediated TGFβ1 activation in the absence of exogenous stimulation, and can be amplified by TGFβ1 activation. Fundamentally, we show for the first time that TGFβ1-induced ITGB6 expression occurs via canonical Smad signalling since dominant negative constructs directed against Smad3 and 4 inhibit ITGB6 transcriptional activity. Furthermore, disruption of a Smad binding site at -798 in the ITGB6 promoter abolishes TGFβ1-induced ITGB6 transcriptional activity. Using chromatin immunoprecipitation we demonstrate that TGFβ1 stimulation of lung epithelial cells results in direct binding of Smad3, and Smad4, to the ITGB6 gene promoter within this region. Finally, using an adenoviral TGFβ1 over-expression model of pulmonary fibrosis we demonstrate that Smad3 is crucial for TGFβ1-induced αvβ6 integrin expression within the alveolar epithelium in vivo. Together, these data confirm that a homeostatic, autocrine loop of αvβ6 integrin activated TGFβ1-induced ITGB6 gene expression regulates epithelial basal αvβ6 integrin expression, and demonstrates that this occurs via Smad-dependent transcriptional regulation at a single Smad binding site in the promoter of the β6 subunit gene. Active TGFβ1 amplifies this pathway both in vitro and in vivo, which may promote fibrosis.